2022
DOI: 10.1021/acs.inorgchem.1c02937
|View full text |Cite
|
Sign up to set email alerts
|

Charge-State Dependence of Proton Uptake in Polyoxovanadate-alkoxide Clusters

Abstract: Here, we present an investigation of the thermochemistry of proton uptake in acetonitrile across three charge states of a polyoxovanadate-alkoxide (POV-alkoxide) cluster, [V 6 O 7 (OMe) 12 ] n ( n = 2–, 1–, and 0). The vanadium oxide assembly studied features bridging sites saturated by methoxide ligands, isolating protonation to terminal vanadyl moieties. Exposure of [V 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(42 citation statements)
references
References 84 publications
(205 reference statements)
4
38
0
Order By: Relevance
“…These signals are consistent with those reported for the acetonitrile-bound, oxygen-deficient POV-alkoxide cluster, [V 6 O 6 (OCH 3 ) 12 (MeCN)](OTf) ( V 6 O 6 1+ ). 24 Similar results were observed with Me 2 HQ. We note improved product conversion at early time points using t Bu 2 HQ as the H-atom source; however, in all reactions, the major product observed is complex V 6 O 7 0 ( vide infra ).…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…These signals are consistent with those reported for the acetonitrile-bound, oxygen-deficient POV-alkoxide cluster, [V 6 O 6 (OCH 3 ) 12 (MeCN)](OTf) ( V 6 O 6 1+ ). 24 Similar results were observed with Me 2 HQ. We note improved product conversion at early time points using t Bu 2 HQ as the H-atom source; however, in all reactions, the major product observed is complex V 6 O 7 0 ( vide infra ).…”
Section: Resultssupporting
confidence: 75%
“…Previous work has reported that the surface basicity of POV-alkoxides is dependent on the oxidation state of the assembly, two factors that influence the BDFE­(E–H), as outlined by the Bordwell equation . This observation led us to hypothesize that terminal oxido moieties in vanadium oxide clusters might also be reactive with H-atoms.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations